EFFICACY OF A NON-LIPOPHILIC ANGIOTENSIN CONVERTING ENZYME INHIBITOR AND ITS POSSIBLE ADVANTAGES - N. A. Mazur (Российский кардиологический журнал)
Efficacy of a non-lipophilic angiotensin converting enzyme inhibitor and its possible advantages.